2021
DOI: 10.1155/2021/5573388
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antibiotic Resistance and Biofilm Formation in Clinical Isolates of Klebsiella pneumoniae

Abstract: Aim. Klebsiella pneumoniae (K. pneumoniae) is an encapsulated Gram-negative bacterium that can lead to 14–20% of nosocomial infections. The ability of biofilm formation in this bacterium decreases the host immune response and antibiotic efficacy. This may impose a huge impact on patients and healthcare settings. This study aimed to evaluate the antibiotic resistance pattern and biofilm formation in K. pneumoniae strains isolated from two major Hamadan hospitals, west of Iran. Methods. A total of 83 K. pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 24 publications
9
11
0
Order By: Relevance
“…The results of virulence genes identi cation showed that all strong bio lm-producers were positive for the mH gene and the presence of mH was signi cantly associated with the capacity of bio lm formation (P = 0.005). This result is consistent with previous studies (Kumabe and Kenzaka 2014; Sei et al 2016;Karimi et al 2021). Also, the statistical analysis proved that the presence of mrkD, mrkA, and wcaG genes with bio lm production is statistically signi cant (P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of virulence genes identi cation showed that all strong bio lm-producers were positive for the mH gene and the presence of mH was signi cantly associated with the capacity of bio lm formation (P = 0.005). This result is consistent with previous studies (Kumabe and Kenzaka 2014; Sei et al 2016;Karimi et al 2021). Also, the statistical analysis proved that the presence of mrkD, mrkA, and wcaG genes with bio lm production is statistically signi cant (P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Sei et al reported that K. pneumoniae isolated from sputum and wound swabs had greater ability to form fully bio lms (Sei et al 2016). While Karimi et al reported that the isolates from tracheal tube were able to form stronger bio lms (Karimi et al 2021). In another study conducted by Cruz-Cordova et al, it was shown that all clinical isolates including urine, blood, catheters, and CSF were bio lm-producers (Cruz-Córdova et al 2014, p.).…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella pneumoniae is a Gram-negative, encapsulated, nonmotile, rod-shaped pathogenic bacterium, and member of the Enterobacteriaceae family that can cause various types of healthcare-associated infections, including bloodstream infections, pneumonia, meningitis, wound or surgical site infections, and urinary tract infections. Klebsiella bacteria are normally found in the human intestines (where they do not cause disease) and are also found in human feces [ 1 ]. K. pneumoniae is second to Escherichia coli the most important opportunistic human pathogen responsible for a wide spectrum of nosocomial and community-acquired infections [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…No significant differences were found in the three categories of biofilm formation (weak, moderate, and strong) in HM-positive and HM-negative strains isolated from patients with hospital- and community acquired infections. The percentages of weak, moderate, and strong biofilm formation of HM-positive and HM-negative strains are higher than those described in K. pneumoniae strains isolated from different clinical origins [ 38 , 39 ]. The high percentage of biofilm formation among HM-positive and HM-negative strains isolated from patients with hospital- and community-acquired infections demonstrates their ability to cause acute infections, since biofilms protect bacteria against the host immune response and antimicrobials [ 40 ].…”
Section: Discussionmentioning
confidence: 69%